Selection bias in estimating the relationship between prolonged ED boarding and mortality in emergency critical care patients. Issue 1 (27th January 2022) - Gardner, Kevin; Gordon, Alexandra June; Shannon, Bryant; Nesbitt, Jason; Wilson, Jennifer G.; Mitarai, Tsuyoshi; Kohn, Michael A.
Abstract: Objectives: Studies have found that prolonged boarding time for intensive care unit (ICU) patients in the emergency department (ED) is associated with higher in‐hospital mortality. However, these studies introduced selection bias by excluding patients with ICU admission orders who were downgraded and never arrived in the ICU. Consequently, they may overestimate mortality in prolonged ED boarders. Methods: This was a retrospective cohort study at a single center covering the period from August 14, 2015 to August 13, 2019. Adult ED patients with medical ICU admission orders and at least 6 hours of subsequent critical care in either the ED or the ICU were included. Patients were classified as having either prolonged (>6 hours) or non‐prolonged (≤6 hours) ED boarding. Downgraded patients were identified, and mortality was compared, both including and excluding downgraded patients. Results: Of 1862 patients, 612 (32.9%) had prolonged boarding; at 6 hours after ICU admission order entry, they were still in the ED. The remaining 1250 (67.1%) had non‐prolonged boarding; at 6 hours after the ICU admission order entry, they were already in the ICU. In‐hospital mortality in the non‐prolonged boarding group was 18.9%. In the prolonged boarding group, 296 (48.4%) patients were downgraded in the ED and never arrived in the ICU. Including these ED downgrades, the mortality in the prolonged boarding group was 13.4% (risk difference ‐5.5%, 95% confidence interval [CI] ‐8.9% to ‐2.0%, P = 0.0031). When we excluded downgrades, the mortality in the prolonged boarding group increased to 17.4% (risk difference ‐1.5%, 95% CI ‐6.2% to 3.2%, P = 0.5720). The lower mortality in the prolonged group was attributable to lower severity of illness (mean emergency critical care SOFA [eccSOFA] difference: ‐0.8, 95% CI ‐1.1 to ‐0.4, P < 0.0001). Conclusions: Excluding critical care patients who were downgraded in the ED leads to selection bias and overestimation of mortality among prolonged ED boarders.